Dispersion-compensating photonic crystal fiber with wavelength tunability based on a modified dual concentric core structure. Issue 12 (12th July 2018) - Chen, Nan; Zhang, Xuedian; Nie, Fukun; Lu, Xinglian; Chang, Min
Abstract: We present a 5-layer air-hole dispersion-compensating photonic crystal fiber (PCF) with a modified dual concentric core structure, based on central rod doping. The finite element method (FEM) was used to investigate the structure numerically. If the structural parameters remain unchanged, a high degree of linear correlation between the central rod refractive index and the operating wavelength can be achieved in the wavelength range of 1.5457–1.5857 μm, which suggests that the operating wavelength can be determined by the refractive index of the centre rod. A negative dispersion coefficient between –5765.2 ps/km/nm and –6115.8 ps/km/nm was obtained by calculation and within the bandwidth of 108 nm (1.515–1.623 μm) around 1.55 μm, a dispersion coefficient of –3000 ps/km/nm can be ensured for compensation. In addition, this proposed PCF also has the advantage of low confinement loss, between 0.00011 and 0.00012 dB/m, and ease of fabrication with existing technology. The proposed PCF has good prospects in dispersion-compensating applications.